If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5p(2)-245=0
We simplify the equation to the form, which is simple to understand
5p(2)-245=0
Reorder the terms in parentheses
+(+10p)-245=0
Remove unnecessary parentheses
+10p-245=0
We move all terms containing p to the left and all other terms to the right.
+10p=0+245
We simplify left and right side of the equation.
+10p=+245
We divide both sides of the equation by 10 to get p.
p=24.5
| 0.3x+0.1=-0.8 | | -3x-43=2(x+2)+8 | | -5x-13=-28 | | 3w-2(4-8w)=8w+25 | | z^2-z+0.25=0 | | 9=-7-3-a+a | | (9y+11)(4y+5)=0 | | 423/16-281/4 | | 5x+38=4(2x+2) | | 6(5-4v)=2(4v-17) | | -3x+20=23 | | 2(4x+3)+1=2x+49 | | -6x/6 | | -2x-20=3(x+1)-8 | | 2(x+4)=x+3 | | 9x+3y=5 | | 8x^2+42x+49=0 | | 8x-4=4x-40 | | 8(4u-7)-8u=-2(u+2) | | 2x+2/6x^2+16x+10 | | -7x-6=-4x-24 | | a(2)-7a+6=0 | | 144w^2-9=0 | | x^2+xy-x=3 | | Y=6x^2+17x-28 | | (1/2)x+9=10 | | 6n(2)+36n+54=0 | | 4(2x-3)+4x=6(2x+5) | | 24x^2+48-72=0 | | 5-3x+4(x-3)=4 | | 5/9+x=6/18 | | v(2)-6v=0 |